The Intron 4 Polymorphism in the Calcium-Sensing Receptor Gene in Diabetes Mellitus and its Chronic Complications, Diabetic Nephropathy and Non-Diabetic Renal Disease - Viera Železníková; Marcela Vedralová; Anna Kotrbová-Kozak; Hana Zoubková; Marie Černá; Ivan Rychlík (Karger Publishers, 2014)
Background/Aims: Calcium-Sensing Receptor (CaSR) significantly affects calcium-phosphate metabolism in kidneys, and it is implicated in the pathogenesis of diabetes mellitus (DM) due to its expression in pancreatic F-cells. The role of CaSR as one of the players in pathogenesis of chronic kidney disease (CKD) has been speculated. Methods: 158 Type 2 diabetic patients divided into three groups according to occurrence and type of kidney complications, 66 nondiabetic patients CKD, and 93 healthy subjects were enrolled into the study to analyze the role of two CaSR polymorphisms (in the codon 990 and in the intron 4) in ethiopathogenesis of DM and CKD. The Type 2 diabetic groups consisted of 48 patients without any kidney abnormalities, 58 patients with diabetic nephropathy (DN), and 52 patients with nondiabetic renal disease (NDRD). The distribution of genotype and allele frequencies was studied using PCR with the TaqMan Discrimination Assay or followed by the Restriction Fragment Length Polymorphism method, respectively. Results: We have found that the intron 4 polymorphism is a risk factor for the development of DM and CKD, except DN, while the codon 990 does not show any disease association. Conclusion: We conclude that CaSR is a general factor in pancreas and kidney pathologies. i 2014 S. Karger AG, Basel